Contributions of Organisational Transparency, Communication Flow and Intrinsic Motivation to Teachers Job Performance in Ogun State Public Secondary School. - Alaba, Adebola O. (NIU Journal of Social Sciences, 2017)
This study sought to determine the joint and relative contributions of organisational transparency, principals’ communication flow and teachers’ intrinsic motivation to teachers’ job performance in Ogun State public secondary schools. This is predicated on the fact that lack of transparency has been the major problem militating against the nation’s development in all spheres of human endeavour. In Nigeria, much attention has not been focused on how organisational transparency individually and jointly combined with other variables to determine the job performance of teachers. The study employed the descriptive research design of the ex-post facto type. One thousand and thirty seven teachers  (1037) in public secondary schools in Ogun State participated in the study. The sampling was done using multi-stage proportional and stratified random sampling techniques. Four instruments were used in collecting data namely; Transparency Factor Questionnaire (TFQ), Principals’ Communication Flow Questionnaire (PCFQ), and Teachers’ Intrinsic Motivation Scale (TIMS) for the independent variable and Teachers’ Job Performance Rating Scale (TJPRS) for the dependent variable.  All the instruments were adapted and pilot- tested and gave validity values of Chronbach alpha values between 0.8246 and 0.8670,  the split- half reliability values ranging from 0.7841 to 0.8824. One hypothesis was formulated and tested. The data collected were analysed using multiple regression analysis. Findings revealed that organisational transparency, principals’ communication flow and teachers’ intrinsic motivation jointly and significantly accounted for 15.1% of teachers’ job performance. Significantly, organisational transparency contributed 3.1%, principals’ communication flow contributed 13.4% and teachers’ intrinsic motivation contributed 3.2% to teachers’ job performance. The study recommended among others that principals should adopt a transparent administrative style and ensure an effective communication flow in their schools; they should also help in enhancing teachers’ intrinsic motivation by motivating excellent performance exhibited by them; government on her part must put in place policies that can enhance transparency in schools and motivate teachers effectively. Key Words: organisational transparency; communication flow;  intrinsic motivation; teachers’ job performance; secondary schools in Ogun State.